실제 대기의 광화학 반응 챔버로 사용되는 테플론 백의 오염도 평가 - 이승복; 배귀남; 이영미; 문길주 (한국입자에어로졸학회, 2013)
Experiments on photochemical reactions of purified air alone in an indoor smog chamber were carried out after flushing Teflon bags with purified air for many hours in order to check the level of contamination on the chamber wall. Ozone concentrations were linearly increased from <4 ppb up to about 8 ppb with irradiation time for four hours. Outgassing of NOx from the chamber wall was found to be less than 1 ppb. New ultrafine particles were formed and grown up to about 70 nm during the photochemical reactions, and then total number and mass concentrations of particles were increased from <10 particles/cm3 up to about 4,000 particles/cm3 and 1.3 ㎍/m3, respectively. The wall conditions of these Teflon bags flushed with purified air might not severly affect the chamber experimental results for photochemical reactions of polluted urban ambient air. The difference of gaseous species between two chambers was 2.4 ppb of ozone at most, indicating that the wall cleaning performance of two chambers was nearly similar.